Inter-muscular coherence in speed skaters with skater's cramp. (February 2023) - Nijenhuis, B.; Tijssen, M.A.J.; van Zutphen, T.; van der Eb, J.; Otten, E.; Elting, J.W.
Abstract: Introduction: Skater's cramp is a career-ending movement disorder in expert speed skaters noted to be a likely task-specific dystonia. In other movement disorders, including task-specific dystonia, studies have found evidence of central dysregulation expressed as higher inter-muscular coherence. We looked at whether inter-muscular coherence was higher in affected skaters as a possible indicator that it is centrally driven, and by extension further evidence it is a task-specific dystonia. Methods: In 14 affected and 14 control skaters we calculated inter-muscular coherence in the theta-band in a stationary task where tonic muscle activation was measured at 10%, 20% and 50% of maximum voluntary contraction. Additionally, we calculated wavelet coherence while skating at key moments in the stroke cycle. Results: Coherence did not differ in the stationary activation task. While skating, coherence was higher in the impacted leg of affected skaters compared to their non-impacted leg, p = .05, η 2  = 0.031, and amplitude of electromyography correlated with coherence in the impacted leg, p = .009, R 2 adjusted  = 0.41. A sub-group of severely affected skaters (n = 6) had higher coherence in the impacted leg compared to the left and right leg of controls, p = .02, Cohen's d = 1.59 and p = .01, Cohen's d = 1.63 respectively. Results were less clear across the entire affected cohort probably due to a diverse case-mix. Conclusion: Our results of higher coherence in certain severe cases of skater's cramp is preliminary evidence of a central dysregulation, making the likelihood it is a task-specific dystonia higher. Highlights: Inter-muscular coherence in skater's cramp suggests a task specific dystonia. Inter-muscular coherence was higher in severely affected skaters. Problems occurred task-specifically while skating. Wavelet coherence provides improved measures in task-specific dystonia in sports.